Effectiveness, Safety, and Economic Comparison of Inhaled Epoprostenol Brands, Flolan and Veletri, in Acute Respiratory Distress Syndrome. Issue 5 (May 2020) - Hawn, Jaclyn M.; Bauer, Seth R.; Wanek, Matthew R.; Li, Manshi; Wang, Xiaofeng; Duggal, Abhijit; Torbic, Heather
Background: No previous studies exist examining 2 inhaled epoprostenol formulations in an acute respiratory distress syndrome (ARDS) patient population.Objective: The study aim was to evaluate a formulary conversion from inhaled Flolan to Veletri to determine the impact on effectiveness, safety, and cost in patients with ARDS.Methods: This was a single-center, retrospective, matched cohort observational study at a tertiary care academic medical center. Patients included were mechanically ventilated, adult patients with ARDS receiving inhaled Flolan or Veletri for ≥1 hour in the intensive care unit.Results: A total of 132 patients were included in the matched cohort. There was no difference detected in change in partial pressure of arterial O2 /fraction of inspired O2 (PaO2 /FiO2 ) ratio after 1 hour of therapy between the inhaled Flolan and Veletri groups (27.2 ± 46.2 vs 30 ± 68 mm Hg, P = 0.78). Significant differences in secondary outcomes included incidence of hypotension (83% vs 95.5%, P = 0.04) and thrombocytopenia (9.1% vs 29.5%, P < 0.01) in the inhaled Flolan and Veletri groups, respectively, with no difference in cost per duration of therapy ( P = 0.29).Conclusions and Relevance: There was no difference in the change in PaO2 /FiO2 ratio after 1 hour of therapy between inhaled Flolan and Veletri in an ARDS patient population. The formulary conversion from inhaled Flolan to Veletri was likely justified.